1987
DOI: 10.1136/oem.44.9.602
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence rates and odds ratios of shoulder-neck diseases in different occupational groups.

Abstract: The aim of the present study was to evaluate the association and impact of occupational exposure and diseases of the shoulder and neck. Prevalence rates, odds ratios, aetiological fractions, and their confidence intervals were computed for pooled and non-pooled data of previous published reports. By comparison with office workers and farmers, dentists had an increased odds ratio for cervical spondylosis (two studies) and for shoulder joint osteoarthrosis. Meat carriers, miners, and "heavy workers" also had sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
186
0
2

Year Published

1992
1992
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(196 citation statements)
references
References 22 publications
8
186
0
2
Order By: Relevance
“…In a physical examination, 15 were diagnosed as having neck or shoulder disorders and 2 were given elbow or hand diagnoses. In an interview their median score for muscle tension was 2.0 (range 0-6), and their median work stress during work was 1.8 (1)(2)(3)(4). During maximal voluntary contraction (MVC) their median force was 134 (52-226) N.…”
Section: Study Groupmentioning
confidence: 99%
“…In a physical examination, 15 were diagnosed as having neck or shoulder disorders and 2 were given elbow or hand diagnoses. In an interview their median score for muscle tension was 2.0 (range 0-6), and their median work stress during work was 1.8 (1)(2)(3)(4). During maximal voluntary contraction (MVC) their median force was 134 (52-226) N.…”
Section: Study Groupmentioning
confidence: 99%
“…This population was of particular interest because of their increased risk for developing shoulder problems. 3,8,9 In addition, we believe that people who do not engage in overhead activities, even though they might not have symptoms of shoulder impingement, may demonstrate abnormal kinematic patterns that could contribute to the development of shoulder impingement if they routinely used their arms in elevated positions. We believed that equal occupational exposure between the 2 groups would improve the potential to detect kinematic or muscle activity differences.…”
Section: Subjectsmentioning
confidence: 99%
“…Frequent or sustained shoulder elevation at or above 60 degrees in any plane during occupational tasks has been identified as a risk factor for the development of shoulder tendinitis or nonspecific shoulder pain. 3,8,9 Evidence relating occupational exposure of frequent or sustained shoulder elevation to shoulder musculoskeletal symptoms is strongest for combined exposure to multiple physical factors, such as holding a tool while working overhead. 9 Multiple theories exist as to the primary etiology of shoulder impingement, including anatomic abnormalities of the coracoacromial arch or humeral head 10,11 ; "tension overload," ischemia, or degeneration of the rotator cuff tendons [12][13][14] ; and shoulder kinematic abnormalities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the incidence of WMSDs is higher among women than men [38][39][40] . Why is this?…”
Section: Gender Differences In the Incidence Of Wmsdsmentioning
confidence: 99%